Analisis Kondisi NEET (Not In Employment, Education or Training) Provinsi Gorontalo dan Profil Demografinya - Zul Fita Lihawa; Muhammad Amir Arham; Boby Rantow Payu (Economic Reviews Journal, 2024)
Gorontalo Province is entering the peak phase of the demographic bonus and socio-economic conditions that are not yet optimal. The high number of unemployed young people is a problem that must be addressed immediately. One of the problems related to this young age condition is the NEET phenomenon. NEET is one of the indicators of the Sustainable Development Goals to determine the level of vulnerability of young people aged 15-24 years in dropping out of school, unemployment, and feeling hopeless in the world of work. This study aims to analyze the NEET picture in Gorontalo Province. The research method used is quantitative descriptive with a cross-tabulation approach (Crosstab). The results of the data analysis show that the distribution of the NEE population in Gorontalo Province is highest in North Gorontalo Regency. This study concludes based on the demographic profile that NEE individuals in Gorontalo generally come from low socio-economic backgrounds, tend to live in rural areas, and have low levels of education.